Neufundlands Wirtschaft vor neuen Aufgaben: Wandlungen im Zusammenhang mit dem zweiten Weltkrieg und der Eingliederung in Kanada - Bartz, Fritz (ERDKUNDE, 1954)
Newfoundland was until very recently an island in which the greater part of the population gained its livelihood from the fisheries, in particular the salt cod industry. However the country's economy has been in process of slow but steady change since 1900, when mining and paper industries became established. Since World War II and federation with Canada in 1949 the fishing industry has undergone considerable modifications. The old type of Labrador schooner and the Banks fishery employing long (trawl) lines have virtually disappeared, their places being taken, in part, by ottertrawl nets. The US-Army and Navy bases have created employment for many Newfoundlanders. The Newfoundland Government, being very much concerned with the low living standard of the fishing population, in particular along the densely populated Northeast Coast, is trying to modify conditions by providing new possibilities for employment through new industries and by changing the character of the fishing economy itself, thereby perhaps anticipating changes, which would probably occur much more disruptively without any governmental interference.